Modification of the structurally the phase state of aluminum alloy as a result of radiation thermal treatment - Prokhorenko, E.M.; Lytvynenko, V.V.; Bryukhovetskiy, V.V.; Shul’gin, N.A.; Kolodiy, I.V.; Tantsyura, I.G.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2022)
The effect of relativistic electron beams on the change in the structure of the 2014 aluminum alloy was studied. The mechanical characteristics (hardness, ultimate strength, conditional yield stress) of the samples were measured before and after irradiation. The influence of phase changes on these mechanical characteristics was investigated. The possibility of cleaning the surface of alloy 2014 using electron beams was studied. The identification of phase inclusions in the aluminum alloy was carried out. The changes in the number of phases that occurred as a result of irradiation with relativistic electron beams were determined. Вивчався вплив дії релятивістських електронних пучків на зміну структури алюмінієвого сплаву 2014. Вимірювалися механічні характеристики (твердість, гранична міцність, умовна межа текучості) зразків до і після опромінення. Досліджувався вплив на ці механічні характеристики зміни фаз. Вивчалася можливість очищення поверхні сплаву 2014 за допомогою електронних пучків. Проводилася ідентифікація включень фаз в алюмінієвому сплаві. Визначалися зміни в кількості фаз, які сталися в результаті опромінення релятивістськими електронними пучками. Изучалось влияние воздействия релятивистских электронных пучков на изменение структуры алюминиевого сплава 2014. Измерялись механические характеристики (твердость, предельная прочность, условный предел текучести) образцов до и после облучения. Исследовалось влияние на эти механические характеристики изменения фаз. Изучалась возможность очистки поверхности сплава 2014 при помощи электронных пучков. Проводилась идентификация включений фаз в алюминиевом сплаве. Определялись изменения в количестве фаз, которые произошли в результате облучения релятивистскими электронными пучками.